2011
DOI: 10.1017/s1368980011002217
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and effectiveness of supplementation with locally available foods in prevention of child malnutrition in Kenya

Abstract: Objective: To establish the operational feasibility and effectiveness of using locally available foods to prevent malnutrition and improve child growth in Kenyan children. Design: Quasi-experimental design with an intervention group of children in all villages in one region and a non-intervention group of children in all villages in an adjacent region. The intervention was the distribution of a monthly food ration for the index child, a separate family ration, and group education on appropriate complementary f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 13 publications
0
45
0
Order By: Relevance
“…In the Siaya, Kisumu, and Busia districts of Kenya, a high prevalence of childhood undernutrition was attributed to low maternal independence and high martial discord as childcare is not only affected by a mother’s direct actions with her child, but also through her social relationships with others because of the assistance that others provide [39]. In terms of food aid, a study in the Yatta district investigated the effectiveness of using local foods to improve the nutritional status of children and found that a small food ration provided to families resulted in a lower prevalence of wasting and underweight compared to control families [40]. Similar to our results, two studies in urban settlements of Nairobi (Korogocho and Viwandani) found that a higher maternal educational status was associated with higher nutritional status of her child [35, 41].…”
Section: Discussionmentioning
confidence: 99%
“…In the Siaya, Kisumu, and Busia districts of Kenya, a high prevalence of childhood undernutrition was attributed to low maternal independence and high martial discord as childcare is not only affected by a mother’s direct actions with her child, but also through her social relationships with others because of the assistance that others provide [39]. In terms of food aid, a study in the Yatta district investigated the effectiveness of using local foods to improve the nutritional status of children and found that a small food ration provided to families resulted in a lower prevalence of wasting and underweight compared to control families [40]. Similar to our results, two studies in urban settlements of Nairobi (Korogocho and Viwandani) found that a higher maternal educational status was associated with higher nutritional status of her child [35, 41].…”
Section: Discussionmentioning
confidence: 99%
“…In Kenya, 35% of children under the age of 5 have stunted growth, with 42% of these children living in Kenya's Eastern Province where they survive off a low energy maize based diet (Tomedi, 2012). These children would greatly benefit from the addition of a microalgae supplement in order to better their physical and neurological development as well as survival.…”
Section: Moejes and Moejes 297mentioning
confidence: 99%
“…The proportion of the child's daily recommended intake of energy provided by the supplementary food varied widely, from 8% to 136%. Seven of the programmes 4,[30][31][32][33][34][35] provided additional rations for the family (to reduce redistribution of the child's supplement).…”
Section: Implementation Of Supplementary Feeding Programmesmentioning
confidence: 99%
“…Four studies found no difference in the incidence of illness between children who received supplementary food and those who did not, while two studies reported that children who received supplementary food were more likely to be unwell. 24,30,33,42,77 A range of illnesses were studied as outcomes, including fever, diarrhoea and respiratory infection.…”
Section: Illness and Deathmentioning
confidence: 99%
See 1 more Smart Citation